How a firm can induce legislators to adopt a bad policy - Dahm, Matthias; Dur, Robert; Glazer, Amihai (Springer, 2014)
This paper shows why a majority of legislators may vote for a policy that benefits a firm but harms all legislators. The firm may induce legislators to support the policy by suggesting that it is more likely to invest in a district where voters or their representative support the policy. In equilibrium, no one vote may be decisive, so each legislator who seeks the firm’s investment votes for the policy, though all legislators would be better off if they all voted against the policy. And when votes reveal information about the district, the firm’s implicit promise or threat can be credible. Unlike influence mechanisms based on contributions or bribes, the behavior considered is time consistent and in line with the low campaign contributions by special interests.